Sofabotik program assistance as a solution to the accumulation of plastic bottle waste - Nurwidiana Nurwidiana; Wiwiek Fatmawati (Universitas Muhammadiyah Magelang, 2022)
As the use of plastic grows in both industry and households, it is becoming a more serious environmental issue. Used plastic bottles of bottled drinking water are one source of plastic waste. This activity designed to educate participants about the dangers of plastic waste and equip them with the skills to turn it into useful items. Counseling and training are the methods used. The program was successful in raising partner awareness of the dangers of plastic waste. Partners also know how to deal with plastic bottle waste by turning it into a sofa with economic value. In addition to the financial benefits, this program allows more and more used bottles to be reused, reducing the amount of plastic waste that is dumped into the environment.